The Effect of Leverage, Independent Commissioners, Audit Committee and Institutional Ownership on Financial Statement Integrity (Empirical Study of Infrastructure Companies Listed on the Indonesia Stock Exchange in 2020 - 2023) - Minanari, Minanari; Azzahra, Davina (Baca Dulu Publisher, 2025)
This study aims to analyze and obtain empirical evidence regarding the influence of Leverage, Independent Commissionerss, Audit Committee, and Institutional Ownership on the Integrity of Financial Statements in infrastructure companies listed on the Indonesia Stock Exchange during 2020–2023. Using purposive sampling, 50 companies were selected from a population of 64. Secondary data were analyzed using descriptive statistical methods with IBM SPSS version 25. The results indicate that Leverage and Institutional Ownership have a significant negative effect on Financial Statement Integrity, while Independent Commissionerss and the Audit Committee show no significant effect.